Porcine reproductive and respiratory syndrome virus 2 hijacks CMA-mediated lipolysis through upregulation of small GTPase RAB18. - Guo-Li Li; Ying-Qian Han; Bing-Qian Su; Hai-Shen Yu; Shuang Zhang; Guo-Yu Yang; Jiang Wang; Fang Liu; Sheng-Li Ming; Bei-Bei Chu (PLoS Pathogens)
RAB GTPases (RABs) control intracellular membrane trafficking with high precision. In the present study, we carried out a short hairpin RNA (shRNA) screen focused on a library of 62 RABs during infection with porcine reproductive and respiratory syndrome virus 2 (PRRSV-2), a member of the family Arteriviridae. We found that 13 RABs negatively affect the yield of PRRSV-2 progeny virus, whereas 29 RABs have a positive impact on the yield of PRRSV-2 progeny virus. Further analysis revealed that PRRSV-2 infection transcriptionally regulated RAB18 through RIG-I/MAVS-mediated canonical NF-κB activation. Disrupting RAB18 expression led to the accumulation of lipid droplets (LDs), impaired LDs catabolism, and flawed viral replication and assembly. We also discovered that PRRSV-2 co-opts chaperone-mediated autophagy (CMA) for lipolysis via RAB18, as indicated by the enhanced associations between RAB18 and perlipin 2 (PLIN2), CMA-specific lysosomal associated membrane protein 2A (LAMP2A), and heat shock protein family A (Hsp70) member 8 (HSPA8/HSC70) during PRRSV-2 infection. Knockdown of HSPA8 and LAMP2A impacted on the yield of PRRSV-2 progeny virus, implying that the virus utilizes RAB18 to promote CMA-mediated lipolysis. Importantly, we determined that the C-terminal domain (CTD) of HSPA8 could bind to the switch II domain of RAB18, and the CTD of PLIN2 was capable of associating with HSPA8, suggesting that HSPA8 facilitates the interaction between RAB18 and PLIN2 in the CMA process. In summary, our findings elucidate how PRRSV-2 hijacks CMA-mediated lipid metabolism through innate immune activation to enhance the yield of progeny virus, offering novel insights for the development of anti-PRRSV-2 treatments.